The ability of local isolates of the fungus, Beauveria bassiana (Bals.) Vuil., to colonize cucumber plants under greenhouse conditions - أحمد, محمد; غزال, ابتسام; رجب, لبنى (Latakia University Journal -Biological Sciences Series, 2021)
The fungus, Beauveria bassiana (Bals.) Vuil., is one of the most important entomopathogenic fungi worldwide. It can be found in a variety of natural and agricultural habitats, and it has recently demonstrated the ability to live endophytically within plants. The present study was conducted to compare the ability of local isolates of the fungus B. bassiana to colonize cucumber plants under greenhouse conditions, using two inoculation methods: seed dusting and seedling drench. Ten different isolates of B. bassiana: B83, B100, B157, B186, B195, B202, B203, B221, B239, and B240 were used. Colonization of the upper plant parts (leaf, petiole, and stem) was calculated after 30 and 60 days of treatment. Other fungal genera present inside the plant were also determined. The results show that all isolates used had the ability to grow systemically and colonize cucumber plants under greenhouse conditions in both treatments. The isolates, B100, B195, and B240, were the most well-established in the plant. Depending on the fungal isolate and the plant part, colonization varied from 0 to 100%. The colonization was highest in the leaf followed by the petiole, and the stem. Moreover, the fungus B. bassiana survived inside cucumber for at least 60 days under greenhouse conditions. Additionally, various genera of fungi were isolated from the cucumber, of which, the genus, Aspergillus, was the most frequent, followed by the genus, Penicillium, with frequency reached 30.7 and 29.5 %, respectively, 60 days post-treatment.